2004
DOI: 10.2186/jjps.48.713
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection in the Oral Cavity of Denture Wearers

Abstract: The results of the present investigation indicate that HPV is present in the oral cavity, especially those of denture wearers, of middle-aged and elderly patients. It is suggested, therefore, that the oral cavity of middle-aged and elderly patients with dentures is a reservoir of HPVs where later HPV-associated diseases, such as oral cancer and other oral lesions, may develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Considering these characteristic of HPV infection, it can be assumed that HPV can easily invade and infect cells of OLP lesions where the oral mucosa is often damaged due to erosion or ulcers. Nishimura et al 44) also reported that HPV infection was frequently observed in the oral mucosa of patients wearing dentures, suggesting that chronic stimulation of the mucosa by the denture and subsequent erosion of the mucosa are the reason for the frequent infection. In the present study, the highest HPV positive rate was observed in the erosive type of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these characteristic of HPV infection, it can be assumed that HPV can easily invade and infect cells of OLP lesions where the oral mucosa is often damaged due to erosion or ulcers. Nishimura et al 44) also reported that HPV infection was frequently observed in the oral mucosa of patients wearing dentures, suggesting that chronic stimulation of the mucosa by the denture and subsequent erosion of the mucosa are the reason for the frequent infection. In the present study, the highest HPV positive rate was observed in the erosive type of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step of the PCR assay, we used the degenerate L1 consensus primers GP5/6 18) and GP5+/6+ 19) , which can detect the presence of DNA of 9 HR-HPV types (16,18,31,33,35,45, 51, 56 and 58) and seven LR-HPV types (1,6,8,11,13,30,32 and 58) ( Table 1). Secondly, the positive PCR samples in the first step of the assay were analyzed by type-specific PCR with primers designed for the detection of HPV types 6, 11, 16, 18 and 33 13) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the positive PCR samples in the first step of the assay were analyzed by type-specific PCR with primers designed for the detection of HPV types 6, 11, 16, 18 and 33 13) ( Table 1). The HPV genotyping procedure employed in this study was confirmed by direct DNA sequence HPV.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations